Impact of grading on steady-state strength. Issue 4 (3rd October 2019) - Linero Molina, S.; Azema, E.; Estrada, N.; Fityus, S.; Simmons, J.; Lizcano, A.
Abstract : In the mining industry, waste dumps are earthen structures typically built by loose waste tipping. They may reach heights of hundreds of metres and undergo large deformations. For this reason, their stability design is based on the steady-state shear strength of the waste material. Waste materials are widely graded and may contain particles of up to metric order. Particle shape depends on the pattern of dissecting discontinuities at the source rock mass and the relation between the size of the fragments and discontinuity spacing. The shear strength of this material is determined in the laboratory using scaled samples with altered particle-size distribution (PSD). However, altering the PSD is known to impact shear strength, and this impact is poorly studied. The representativeness of laboratory parameters obtained from scaled samples is thus arguable. Discrete-element simulations are used here to investigate steady-state shear strength changes with the alteration of the PSD when particle size and shape are correlated. It is observed that shear strength changes result from the variation of the particle shapes induced by the alteration of the PSD. Consequently, identifying size−shape correlations and their potential impact on shear strength is of paramount importance when scaling materials for laboratory testing.